Using Feminism Approach To Comparison The Main Characters The Queen in The Novel Snow White and The Seven Dwarfs - Krismayani, Ni Putu Wiwik (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to find out the similarities and differences of "The Queen" characters from novels and comics novels and comics The Snow White and The Seven Dwarfs. In addition to finding out similarities and differences, this research also examines the character analysis of "queen" using the feminism approach. This study uses the novel The Seven Dwarfs by Ladybirds Tales in 1969 and Snow White and The Seven Dwarfs by Regis Maine was first published in 2012. Both versions of Snow White and Seven Dwarf have several differences that we can get in the story. The method used in this study is a descriptive qualitative method. The results show that Snow White and Seven Dwarfs novels and comics, "The Queen" have some similarities in the nature of comics and novels and comics such as "Narcism". Likewise, in the differences in characters that look striking in nature owned by "The Queen" in the novel with those in the comics. For example in the novel one of the characteristics of "The Queen" in the novel is "smart" but in the comic "Sly", the two words have an intense meaning. And the latest research results showing that a. The character of the queen represents the ability of a woman to become a leader. The queen succeeded in replacing the king of the real position was the first position in the kingdom. He proved that the woman could also rule their own kingdom. Before the nineteenth century, women around the world were not allowed to be leaders. Which shows that the queen’s representative of a woman’s ability to become a leader. Before the nineteenth century, women around the world were not allowed to be leaders.